Glycodelin is a potential biomarker for malignant tumors - M. V. Mnikhovich; M. A. Shekhter; T. V. Bezuglova; K. Kh. Skafi; K. A. Artemyeva; E. S. Mishina (Сибирский онкологический журнал, 2023)
Objective of the study to analyze and summarize the available data on the role of glycodelin in carcinogenesis and its expression in various cancers.Material and Methods. A literature search was conducted in Medline, PubMed Central, NCBI databases in the time interval from January 1983 to October 2019 using the key words glycodelin and cancer. Of the 104 publications found, 21 were used to write the review.Results. This paper presents the overview of the findings in current research focusing on the properties of glycodelin, the major lipocalin protein of the human reproductive system. Some lipocalins are known to play a key role in cancer development as well as influence signaling pathways in the regulation of cell motility, differentiation and neovascularization. Most likely they can be used as cancer markers. Glycodelin A is determined in serum and, due to its special immunoregulatory properties, can serve as a useful prognostic marker and a promising target for future anti-cancer therapies. The presence of glycodelin A in breast cancer tissue is known to be mostly linked to a better prognosis than is attributed to glycodelin-negative tissue, as glycodelin is a protein typical of differentiated tissue. On the other hand, glycodelin might play a role in neovascularisation, thereby promoting tumor growth. Glycodelin is a biomarker of aggressive malignant pleural mesothelioma and a prognostic biomarker of metastatic non-small cell lung cancer at late stages. Glycodelin hyperexpression is associated with brain metastasis in lung adenocarcinoma, and its determination can be used as an additional prognostic factor.Conclusion. The review refects basic scientifc data and results of clinical trials, as well as identifes future prospects that allow the development of new methods for cancer detection and treatment. It should be noted that glycodelin plays an important role in tumor development, progression, angiogenesis, and the formation of distant metastases, and therefore can serve as a useful diagnostic and prognostic marker. Further studies of the functional properties of glycodelin are needed to develop promising strategies in cancer therapy.